Late glacial and Holocene landscape change and rapid climate and coastal impacts in the Canal Beagle, southernmost Patagonia - McCulloch, R. D.; Mansilla Andrade, Claudia Andrea; Morello Repetto, Flavia; De Pol Holz, Ricardo Hernán; San Roman Bontes, Manuel Julio; Tisdall, E.; Torres Elgueta, Jimena Andrea (My University, 2019)
Palaeoenvironmental data for the Late Glacial and Holocene periods are provided from Caleta Eugenia, in the eastern sector of Canal Beagle, southernmost Patagonia. The record commences at c. 16 200 cal a bp following glacier retreat in response to climatic warming. However, cooler conditions persisted during the Late Glacial period. The onset of more temperate conditions after c. 12 390 cal abp is indicated by the arrival of southern beech forest and later establishment at c. 10 640 cal abp, but the woodland growth was restricted by lower levels of effective moisture. The climate signal is then truncated by a rapid marine incursion at c. 8640 cal abp which lasted until a more gradual emergence of the coast at c. 6600 cal abp. During this period the pollen record appears to be dominated by the southern beech woodland. A punctuated hydroseral succession follows the isolation of the site from the sea leading to the re-establishment of a peat bog. Between c. 5770 cal abp and the present there were several periods of short rapid climatic change leading to drier conditions, probably as a result of late Holocene periods of climatic warming.
Keywords: pollen analysis; pollen preservation; sea level change; southern westerly winds; tephrochronology